ROLE OF CENTRAL HEMODYNAMIC PARAMETERS, INTIMAL MEDIAL THICKNESS AND ENDOTHELIAL DYSFUNCTION IN CHILDREN WITH RENAL ARTERIAL HYPERTENSION - I. S. Kostyushina; O. V. Komarova; A. M. Mazo; T. V. Margiyeva; I. V. Dvoryakovskiy; A. N. Tsyigin (Union of pediatricians of Russia, 2013)
The increase in arterial hypertension is one of the most sensitive markers of the renal affection grade, including patients without chronic renal diseases; its rate is in inverse proportion to renal functions. Left ventricular hypertrophy development at chronic renal disease results from the development of increased left ventricular afterload and end diastolic pressure influence; it is a compensatory mechanism, which is closely interconnected with mortality from cardiovascular diseases. Echocardiography is the most widely used method of evaluating the condition of central hemodynamics both in adults and children with arterial hypertension. However, echocardiography does not give the researcher any complete presentation of the cardiovascular system's affection and the consequences of it in the setting of a progressing arterial hypertension. Detection of changes in the arterial wall (intimal medial thickness) and endothelial dysfunction is used to estimate the risk of developing such complications. Ultrasonic diagnostics allow to assess the wall's structure, vascular lumen and determining the intimal medial thickness. Data from a range of foreign and domestic studies allows to suggest that the level of endothelin-1 in the blood serum and its excretion with urine may reflect the renovascular damage severity. The article presents a literary review on the given issue.